Differential genomic alterations in normal and cancerous lung cells in response to chronic inflammation - Wu, Feng-Chang; Lai, Liang-Chuan; Kuo, Yu-Ho; Lee, Yung-Hua; Hsu, Fang-Han; Shen, Cheng-Ying; Chuang, Eric Y.; Tsai, Mong-Hsun (Translational Cancer Research, 2013)
Although chronic inflammation increases the risk of carcinogenesis, there have been few reports of genome-wide screening for chromosomal alterations and DNA damage, such as mutations and strand breaks, induced by chronic inflammation. This study utilized high-resolution comparative genomic hybridization to detect copy number variations (CNVs) between normal and cancerous lung cells treated with tumor necrosis factor-alpha (TNF-α) for 24 weeks to induce chronic inflammation. Ingenuity Pathway Analysis was used to analyze the functions of genes located at the common CNV regions that were induced by chronic inflammation. The results shown that TNF-α induced more CNVs in normal lung cells than in cancerous lung cells. Moreover, Ingenuity Pathway Analysis was used to analyze the function of genes located at the common CNV regions get involved in cancer progression, DNA repair and inflammatory disease. In conclusion, chronic inflammation might be one of a set of factors which transform normal lung cells into tumor cells.